Argument Ellipsis and Scope Economy in Japanese. (17th August 2019) - Maeda, Masako
Abstract: In this article, I show that in Japanese, while some focus elements obligatorily take wide scope with respect to scope‐bearing predicative heads, argument ellipsis reverses this scope possibility, so that narrow‐scope interpretation of the focus element is obligatory. I further show that Scope Parallelism (Fox 2000) overrides this narrow‐scope requirement for elided arguments; when the antecedent clause exhibits scope interaction, the elided clause shows the parallel wide‐scope option. I argue that such scope possibilities fall out from the interaction of the derivational‐PF‐deletion analysis of ellipsis (Takahashi 2013, 2017), the Morphological Merger of predicative heads (Shibata 2015), and Scope Economy and Parallelism (Fox 2000).